PENGARUH KUALITAS PELAYANAN KARYAWAN, PERSEPSI HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN (Studi pada Mahasiswa Universitas Muhammadiyah Semarang Pelanggan JNE) - Astono, Ari Dwi; Haryani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
The aim of this research is to analyze the influence of employee service quality, price perception, and location on customer satisfaction (study of students at Muhammadiyah University, Semarang, JNE customers. The data collection method uses a questionnaire, the sampling technique is accidental sampling. A total of 100 respondents are JNE customers in the city of Semarang Based on testing, employee service quality variables have a positive and significant effect on customer satisfaction. Price perception has a positive and significant effect on customer satisfaction.